Avaliação da gestão de resíduos da construção civil no município de Foz do Iguaçu-PR - Albuquerque, Marilan Cristina (2018)
The performed activities during this work concentrated on mounting a workbench (with an impulse source, a transformer and an oscilloscope) and on the assays using those equipments planning to analyze the transformers frequency response function sensibility to faults, mainly mechanical faults. First, a referential search was done aiming to include this work on the scientific context that deal with this subject, to build the research’s line and to survey the concerning bibliography. Then the equipment and the disposition of themselves were normalized and followed by the assays. Finally, the practical got concentrated on algorithms’ programming of signal processing to improve the frequency response analysis, including routines of specific marks that helps this kind of analysis and the dynamic model of the used transformer.